Observation of a re-entrant phase transition in the molecular complex tris(l2-3, 5-diisopropyl-1, 2, 4triazolato-j2N1:N2)trigold(I) under high pressure. (2016) - Woodall, Christopher H.; Christensen, Jeppe; Skelton, Jonathan M.; Hatcher, Lauren E.; Parlett, Andrew; Raithby, Paul R.
No abstract available